Carbon isotopes, palynology and stratigraphy of the Santonian–Campanian boundary: The GSSP auxiliary sections, Seaford Head (England) and Bocieniec (Poland), and correlation between the Boreal and Tethyan realms - Jarvis, I; Pearce, MA; Monkenbusch, J; Jurkowska, A; Ullmann, CV; Dubicka, Z; Thibault, N (Cretaceous Research, 2022)
This is the final version. Available on open access from Elsevier via the DOI in this record Data availability: Stable isotope data and palynology counts are provided in Appendix B Supplementary data Tables 1 - 3. The stratigraphy and palynology of the upper Santonian–lower Campanian (Uintacrinus socialis–Gonioteuthis quadrata zones) Newhaven Chalk are described for the Campanian auxiliary GSSP section at Seaford Head, England. A new high-resolution bulk-sediment carbonate carbon stable-isotope (δ13Ccarb) curve provides the basis to refine the carbon-isotope event (CIE) stratigraphy of the section. Results are compared to a complementary palynological study of a second Campanian auxiliary GSSP section (U. socialis–O. pilula zones) at Bocieniec, Poland. Palynological assemblages are dominated by organic-walled dinoflagellate cysts (dinocysts; 208 taxa) at both sites. A stratigraphic framework is established via review of published lithostratigraphic, macrofossil, foraminifera and calcareous nannofossil records from the study sites. Carbon isotope curves with 13 major named CIEs provide a basis for correlation of Seaford Head and Bocieniec to sections at: Trunch, England; Poigny, France; Lägerdorf, Germany; and the Campanian GSSP at Gubbio, Italy. Correlations are constrained by biostratigraphic records, including dinocyst events. The Late Santonian δ13C Event (LSE, previously termed the Santonian–Campanian Boundary Event, SCBE) provides a key correlation level between Boreal and Tethyan sections and enables the placement of base Campanian markers: extinction levels of the crinoid Marsupites and the planktonic foraminifera Dicarinella asymetrica; the first appearance of the calcareous nannofossil Aspidolithus parcus parcus; and the C34n/C33r magnetozone boundary (the primary Campanian marker), in both Boreal and Tethyan sections. A holostratigraphy for the Santonian–Campanian boundary interval that integrates CIEs, macrofossils, benthic and planktonic foraminifera, calcareous nannofossils, dinocysts and ...